Methodological issues of developmental psychology in professors historical heritage of traditional universities of Ukraine - Vlasovа, O. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
In the article the author vision of the relevance and importance of "rediscovery" of scientific and psychological legacy of traditional universities professors Ukraine – period of the nineteenth century. It is shown that the formation of modern national methodology of psychology as an independent branch of psychological and pedagogical knowledge has profound scientific, psychological and philosophical roots in the research of scientists oldest universities in Ukraine (Kharkiv, Kyiv and Odessa). Their works were in the origins of scientific psychology and national psychology schools recognized not only in Ukraine, but Russian Empire, of which at that time was all Ukrainian science.
Keywords: national psychological school; methodology; developmental psychology; theoretical psychology; experimental psychology; complex method; genetic approach